Perinatal health inequalities between Canadian-born and foreign-born women in Canada: a decomposition analysis - Seungmi Yang; Jay S Kaufman; Gabriel D Shapiro; Tracey Bushnik; Melia Alcantara; Sam B Harper; Zoua Vang; Angela Mashford-Pringle (BMJ Public Health, 2025)
Background Foreign-born mothers are generally believed to experience better perinatal outcomes than Canadian-born mothers, despite relatively lower socioeconomic status. However, the magnitude and direction of inequalities by nativity status vary across outcomes. Little is known about factors contributing to the health inequalities by nativity status across different perinatal outcomes. Thus, we aim to examine the direction and magnitude of inequalities by nativity status across perinatal outcomes and estimate the contributions of select individual-level characteristics to the inequalities in Canada.Methods Using 132 639 singleton births from the 2016 Canadian Birth-Census Cohort, we estimated the risk of preterm birth (PTB), small-for-gestational-age (SGA) and large-for-gestational-age (LGA) birth, stillbirth, and infant and neonatal death by maternal nativity status. We estimated the contribution of maternal race, maternal and paternal education, paternal nativity status and employment, family income and homeownership, as well as maternal age, marital status, activity limitations and parity to inequalities specific to each outcome, using Kitagawa’s decomposition method.Results Compared with Canadian-born mothers, foreign-born mothers experienced higher rates of all outcomes examined (eg, 627 (95% CI 608, 646) PTBs per 10 000 live births among foreign-born mothers vs 580 (568, 592) among Canadian-born mothers), except for LGA births (677 (648, 706) per 10 000 for foreign-born vs 1006 (959, 1054) for Canadian-born mothers). Non-White maternal race explained the largest proportion of the observed differences for non-fatal outcomes, while the highest income quartile explained the most for the differences in fatal outcomes.Conclusion Foreign-born women fared worse than Canadian-born women for all adverse perinatal outcomes examined apart from LGA births. Our results highlight differential contributions of determinants to perinatal health inequalities by maternal nativity status across outcomes.